PENERAPAN PEMBELAJARAN DIFERENSIASI PADA MATERI KONSEP GEOGRAFI MELALUI PROBLEM BASED LEARNING (PBL) KELAS X4 SMAN 4 MATARAM - Emiliyati (Yayasan Baru Haji Samsudin, 2023)
The Minister of Education and Culture for Research and Technology of the Republic of Indonesia emphasized that the ideals of learning in Indonesia are to create learning that is in favour of students, knowing that it liberates thinking and student potential. Efforts to adapt the learning process in class to meet the learning needs of each student. This research aims to learn how to apply differentiation learning in geography concept material through problem-based learning to X.4 SMAN 4 Mataram. Then this study used a descriptive method after identifying the forms of implementation of percentages and group collaboration and explaining whether the student results were excellent. The results of this study indicate that the application of Differentiated Learning Based on Problem-Based Learning can produce a Pancasila learning profile and increase student motivation and learning outcomes. I implemented the learning design in class X4 SMAN 4 MATARAM to improve enthusiasm, motivation and student learning outcomes following the profile of Pancasila students. Thus the implementation of Differentiated Learning Based on Problem-Based Learning can be carried out well, achieving learning objectives and applying student learning profiles by identifying. Mapping student learning needs naturally and efficiently and carrying out process assessments in groups and individually. When evaluating understanding individually, it is proven that the results/scores achieved are well above average